Examining Academic Self Efficacy to Achieve Student Academic Performance: Evidence from Computer-Based Training - Arika Palapa (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to investigate the impact of mastery goal orientation (MGO) and self-directed learning (SDL) on academic performance via academic self-efficacy (ASE). As a learning medium, computer-based training (CBT) attempts to boost student confidence. The study used a quantitative approach, with 142 merchant marine school students serving as participants. The questionnaire was used as a research tool to collect data. To assess and measure variable relationships, research data was examined using structural equation modeling. According to the findings of the study, MGO and SDL have a direct impact on ASE and academic achievement. The study revealed that ASE mediated MGO and SDL in relation to academic achievement. Individual ambition to acquire information and competence results in ASE, which indicated students' confidence. CBT allows students to broaden their learning interests. SDL and CBT complement each other in a mutually beneficial way. CBT is a learning tool; nevertheless, without SDL, it will be ineffective in improving academic achievement. SDL without CBT is less effective since students are unable to explore a broader range of information and expertise. When students use CBT as a learning medium, they frequently study and practice, gaining more knowledge and expertise. CBT is thought to be an effective learning medium for increasing student academic confidence and performance.